Manual práctico de operación y mantenimiento preventivo para despulpadoras de café de cilindro horizontal, marcas Enco y Penagos hermanos, en el municipio de Yacuanquer Nariño. (2021)
In this project, a practical preventive maintenance and operation manual for electromechanical coffee pulpers is prepared, based on the UNE-EN 13460 maintenance standard and the LEM preventive maintenance methodology. The work is carried out in the municipality of Yacuanquer (Nariño), to improve performance and reduce the appearance of failures in pulping machines. In the same way, it will serve as a guide to understand the functioning and operation of these machines by small coffee producers. The importance of the project lies in the fact that many of the machines used have been modified in order to replace the manual crank operating system with another that uses an electric current motor. For this reason, the existing manuals do not respond to the current needs of coffee growers. Finally, the construction of the manual seeks to improve the pulping process so that coffee growers sell coffee at a higher price, improving quality and the level of production.